DESTINASI JURUSANPENDIDIKAN GURU RAUDHATUL ATFHAL (PGRA) FAKULTAS ILMU TARBIYAH DAN KEGURUAN IAIN SULTAN AMAI GORONTALO TAHUN 2020 - Abdurrahman R Mala (Irfani (e-Journal), 2018)
Each level of education should have competent human resources in order to create a quality output. That later became one of the goals of establishing PGRA Prodi at the Faculty of Science and Teaching Tarbiyah IAIN Sultan Amai Gorontalo. Spirit to create a quality output that is contained in the vision PGRA be excellent courses, reliable, innovative, dignified in preparing candidates for professional educators Raudhatul RA and characterized Islam.Kedudukan Early Childhood Education (ECD) in the National Education system is very strategic, to develop human resources. Qualification for early childhood in Indonesia consists of three channels, namely formal, non-formal and informal. As stated in Law No. 20 Year 2003 on National Education System, that early childhood education in formal education shaped Kindergarten (TK), Raudhatul RA (RA) or other equivalent form. To track non-formal education in the form of group play (Play Group), TPA (TPA) or other forms sejenis.Serta to track informal education in the form of education which is obtained from family or society. Therefore, in the future Prodi PGRA ideals can be realized not only in the conceptual realm, but also in the realm of praxis.